Availability of comprehensive services in permanent supportive housing in Los Angeles. (6th October 2017) - Henwood, Benjamin F.; Harris, Taylor; Woo, Darlene; Winetrobe, Hailey; Rhoades, Harmony; Wenzel, Suzanne L.
Abstract: Studies have often described a specific model or models of permanent supportive housing (PSH), yet few studies have systematically examined what services are typically offered to PSH tenants in any given service system and how those services are offered. Using telephone surveys from 23 PSH agency supervisors and qualitative data collected from 11 focus groups with 60 frontline providers and 17 individual interviews with supervisors from a subset of surveyed agencies—all of which were completed between July 2014 and December 2015—the goal of this study is to better understand what services are being offered in PSH organisations located in Los Angeles and what barriers frontline providers face in delivering these services. Survey findings using statistical frequencies suggest the existence of robust support services for a high‐needs population and that single‐site providers may offer more services than scatter‐site providers. Qualitative thematic analysis of interview and focus group transcripts suggests services may be less comprehensive than they appear. If PSH is to be regarded as an intervention capable of more than "just" ending homelessness, further consideration of the provision of supportive services is needed.